Os referenciais teóricos da área de fundamentos da educação do PPGE/UFSCar: um estudo epistemológico e bibliométrico da produção científica (1993 a 2007) - Coelho, Marcio (2013)
The central theme of this research consists on the theoretical foundation research in Education. The overall objective was to realize a bibliometric and epistemological analysis of the doctoral theses of the Post-Graduate Program in Education UFSCar, to determine the epistemological paradigm that predominated in such research and thus explain the relationship between the production of scientific PPGE-UFSCar and the changes that occurred in the socio-historical context and also in research on education in Brazil from the 1990s. The empirical research that has limited the scientific production of the PPGE Doctoral Course in Area of Concentration in Foundations of Education, the theses defended in the period between 1993 and 2007, totaling 55 theses. As the theoretical framework, although this work presents the different epistemological paradigms that underlie research in Education, was designed specifically for Dialectical Historical Materialism. Regarding methodology, this research is exploratory and descriptive, it was dedicated to identify and analyze the scientific production selected. For this end, we employed the following techniques: a) bibliometric analysis to treat and analyze quantitatively the scientific consist of the 55 theses; b) content analysis to determine the theoretical and methodological framework that guided the research techniques as well as epistemological, ontological and ethical present in the process of knowledge production; c) analysis of questionnaires completed by faculty advisors, and its main publications, expanding the discussion on the theoretical present in the production of scientific PPGE. Sources of research data were: a) the theses obtained in Community Library UFSCar and file PPGE-UFSCar as well as the Digital Library of Theses and Dissertations of BCo/UFSCar; b) the Bank of Theses and Terms Indicators of the CAPES, which provided information about thesis bibliometric; c) the curricula of Plataforma Lattes of doctoral students and faculty mentors; d) questionnaires answered by faculty advisors and their major publications. The search result is provided in three parts, the first being a historical overview of educational research in Brazil, located in the educational context and broader social, then notes on the philosophical foundations of the major paradigms used in educational research, and finally the third part presents the elements of analysis of scientific production, the object of the research context, and the procedures and results of analysis of doctoral theses. Results reveal the dominance of the paradigm of Historical Materialism Dialectic, used in over 63 % of the theses, followed by post-modern trends, used in 30 % of searches, and Phenomenology, used in three theses. No thesis used Positivism as epistemological paradigm. These ratings were corroborated by the epistemological, ontological and ethical assumptions, as well as by references to authors and works connected to these paradigms.